Pola Komunikasi Ammatoa dalam Melestarikan Kearifan Lokal Melalui Nilai Kamase-Masea di Kajang - Suryani Musi; Fitriana Fitriana (Jurnal Komodifikasi, 2019)
The purpose of this research is to find out the communication patterns carried out by Ammatoa to the Kajang community, as well as to know the Kamase-masea value system in maintaining the Kajang cultural value. This study uses qualitative research with a symbolic interactional approach. The author uses a purposive sampling technique to obtain informants. Data used through in-depth interviews, literature study, observation and internet searching, with data analysis techniques using the Miles & Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that Ammatoa communicates with the Kajang Dalam community face to face and without restrictions because in the area they are not permitted to use communication media, especially mass communication media. However, when Ammatoa wants to communicate with the Kajang Luar community, Ammatoa is assisted by customary stakeholders (Galla), meaning that communication takes place through intermediaries by word of mouth, in this case the communication pattern used by Ammatoa is to use circular communication patterns. While the communication process carried out by Ammatoa to the general public is to use direct communication, but usually through intermediaries for language translators for those who do not understand the Konjo language used by Ammatoa. The application of the kamase-masea value system in the Kajang culture can be seen from the simple lifestyle adopted by the Kajang Dalam community, such as not using sandals, and limiting the entry of modernization in the customary area. This can also be seen from residential areas, household appliances, and clothing used. Ammatoa and the community in the Kajang Customary Area are communities that limit the entry of all things that have the smell of technology so that the preservation of their customs is still maintained today. This can be an example for other communities so that they are also able to limit the entry of technology that can fade customs.